872Novel approach to estimating sex differences unconfounded by familial factors from studying male-female twin pairs. (2nd September 2021) - Calais-Ferreira, Lucas; Mendonça, Everton; Li, Shuai; Barreto, Marcos; Hickey, Martha; Dite, Gillian; Ferreira, Paulo; Scurrah, Katrina; Hopper, John
Abstract: Focus of Presentation: Males and females differ substantially in their exposures and outcomes across the life-course. Previous research into sex differences has been limited by an inability to account for inter-individual differences in genetic factors and in their early-life environment. Studying within male-female twin pair differences offers a unique opportunity to address these weaknesses that has not yet been exploited. Findings: We studied linked health administrative data for 28, 054 newborn Brazilian male-female twin pairs. Using random-effects logistic regression, we found that males had 1.61 (95% CI: 1.38– 1.90, P <0.001) times higher risk of early neonatal mortality (first 6 days of life) compared with their female co-twins, after adjusting empirically for birthweight and matching for gestational age and, by design, for unmeasured familial factors including on average 50% of genetic factors. From analysing within-pair differences in genome-wide DNA methylation in blood samples for 55 Australian adolescent male-female twin pairs, we found that 1, 227 DNA methylation sites were more methylated in females while only 157 sites were more methylated in males ( P <10 -6 ). We also found weak evidence suggesting that males have older DNA-methylation-based biological age than females ( P =0.2). Conclusions/Implications: Sex differences not explained by familial confounders exist for neonatal mortality in newborns and for DNA methylation in blood during adolescence. Key messages: Analysing the within-pair differences of male-female twin pairs brings novel and important strengths to the study of sex differences, helping mitigate bias from uncontrolled familial confounding caused by genetic and environmental factors.